(untitled) (JBN (Jurnal Bedah Nasional), 2026)
Background: The hand is a highly complex anatomical structure essential for functional, sensory, and aesthetic performance. Burn injuries frequently involve the hand and often result in contractures, deformities, and functional impairment requiring reconstructive surgery. A thorough understanding of surgical anatomy is fundamental for optimizing reconstructive outcomes. Objective: This literature review aims to summarize the surgical anatomy of the hand and its relevance in burn reconstruction and post-burn contracture management. Methods: A narrative literature review was conducted using anatomical and surgical references. Anatomical structures, mechanisms of contracture formation, and reconstructive surgical strategies were synthesized. Results: The hand consists of integrated integumentary, musculoskeletal, neural, and vascular systems that enable fine motor control. Burn injuries commonly result in skin loss, scar contracture, tendon adhesion, joint stiffness, and deformities such as boutonniere deformity and syndactyly. Surgical management includes contracture release, Z-plasty, skin grafting, and flap reconstruction. Conclusion: Comprehensive knowledge of hand surgical anatomy is crucial for effective burn reconstruction. Detailed anatomical understanding allows surgeons to select appropriate surgical approaches and improve functional and aesthetic outcomes.